The Relationship Between Dietary Fiber Consumption Patterns and Physical Activity with the Incidence of Hemorrhoids - Gustomi, Mono Pratiko; Mahmudah, Rifaatul (Kontribusia : Research Dissemination for Community Development, 2024)
The purpose of this study was to explain the relationship between fiber food consumption patterns and physical activity with hemorrhoidal events. This study used a retrospective correlational analytic study design. The population in this study were patients with signs and symptoms of hemorrhoids in the General Surgery Specialist Poly of Petrokimia Gresik Hospital as many as 89 respondents, with sampling using purposive sampling and 72 respondents were obtained. Data analysis using the Chi-square test. Data collection using a fiber food consumption pattern questionnaire, a physical activity questionnaire, and the results of the diagnosis of the General Surgeon Specialist in the respondent's Medical Record. The results of statistical analysis with the Chi-square test with a significance level of alpha <0.05 obtained a p-value of 0.001 and 0.000, which means that there is a relationship between fiber food consumption patterns and physical activity with hemorrhoidal incidence. Insufficient fiber food consumption patterns cause feces to settle longer in the rectum so that the consistency of feces will become harder. This condition stimulates a straining reflex to appear during defecation, causing hemorrhoids. Meanwhile, a pattern of physical activity that is lacking causes continuous and repeated pressure on the lower part of the digestive tract, causing vascularization to be less than optimal and causing hemorrhoids. This study is expected to be a reference for hospitals to be able to add educational media and health promotion as an effort to prevent hemorrhoidal incidence in the community and prevent recurrence in patients who have undergone hemorrhoid treatment.